AN AUTOMATIC FIXTURE DESIGN SYSTEM FOR CREATING PRISMATIC PARTS - Al-Ahmari, Abdulrahman; Khan, Awais Ahmad; Abouel Nasr, Emad Samir; Kamrani, Ali (The South African Journal of Industrial Engineering, 2014)
A modular fixture system is a flexible alternative to a dedicated fixture. In this paper, an automatic modular fixture design system is suggested for creating prismatic parts. The system contains fixture planning, fixture modelling, and fixture assembly. The part geometrical database and process plans are considered as inputs to the system. A rule- based method is applied to assign the feasible locating scheme and the locating and clamping datum. The search strategy is designed to determine the most suitable locating and clamping points. The final fixture assembly is made with the standard fixture components using the CATVBA Editor inside CATIAV5. The proposed methodology is successfully validated with a case study.